Perancangan Sistem Informasi E-Raport Berbasis Web Di MTS Daruth Tholibiin Jatisari - Ma'ruf Hasan Nurwahid; Budiman Budiman; Winarti Winarti (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
Information technology functions significantly in improving the quality of an institution, not only as a process of automation of data access, technology also produces the accuracy and speed of an integrated system, so that the management process will be more efficient. Raport is a report on the results of student evaluation based on the period and subjects accompanied by an evaluation of character, behavior and attitude. MTs Daruth Tholibiin is one of the learning institutions that uses technology as a support for learning activities, but the processing of grade information is still manual and stored in separate archives so that it has a bad impact, namely inaccurate information and loss of information. From the explanation above, it is needed to design a website-based e-raport data system that is expected to help in managing student evaluation information. This system design uses the Waterfall model, using MySQL for database and PHP as the programming language. The outcome on this research is an e-raport information system can be facilitate educational institutions in managing student learning outcomes. Sourced from the results of Black Box method testing, it shows that this information system is in accordance with its usefulness.